2020
DOI: 10.1007/s13592-020-00806-w
|View full text |Cite
|
Sign up to set email alerts
|

Mild thermal stress does not negatively affect immune gene expression in the bumblebee Bombus terrestris

Abstract: Body temperature changes can modify an insect's ability to fight infections by altering its immune activity. This work evaluated the impact of mild cold and heat thermal stress on the expression of different immune and heat shock genes in the species Bombus terrestris . Additionally, a thermal treatment was repeated under starvation to analyze a possible compromise of immune gene expression in favor of a thermal stress response when energetic resources are limited. Results pointed to a role of Hsc70 and Aha1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…However, a recent study found that immune responses were not downregulated in bumblebees reared at 38°C [48]. Furthermore, we lack evidence that bumblebees can discriminate between their own symbiont strains and those from other Bombus, immunologically or otherwise.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, a recent study found that immune responses were not downregulated in bumblebees reared at 38°C [48]. Furthermore, we lack evidence that bumblebees can discriminate between their own symbiont strains and those from other Bombus, immunologically or otherwise.…”
Section: Discussioncontrasting
confidence: 57%
“…Each container was provided with 10 ml of sterile 50% sugar syrup and 500 mg of sterile pollen dough (gamma-irradiated honeybee pollen mixed with sterile 50% sugar syrup). Microcolonies were reared in one of two incubators (Percival Scientific, model I36NL) set at either 29°C, representing a typical bumblebee rearing temperature [32,[46][47][48], or at 35°C, a temperature typical of A. mellifera hives [26]. The pollen lump was replaced on the third day of rearing.…”
Section: (E) Colonization Experimentsmentioning
confidence: 99%
“…( 2022 ) applied thermal tolerance data from other studies and noted a relationship between heat tolerance and several climatic variables in five North American bumble bee species. Differential heat tolerance in bumble bees may be conferred through differences in molecular heat shock response (Blasco‐Lavilla et al., 2021 ; Kuo et al., 2023 ; Pimsler et al., 2020 ), interspecific differences in heat shunting by means of counter‐current exchange between the thorax and abdomen (cf. Heinrich, 1976 ; Heinrich & Vogt, 1993 ), or through other physiological adaptations such as shifting metabolism or potential for evaporative cooling (Johnson et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stress has a large impact on organismal physiology, which can scale up into devastating ecosystem level effects such as the bleaching of coral reefs (Donovan et al, 2021) or the increase in infectious disease (Hector et al, 2021; Indhumathi & Sathesh Kumar, 2021). Temperature can directly alter the immune response of organisms in both positive and negative ways (Blasco‐Lavilla et al, 2021; Murdock et al, 2012; Paaijmans et al, 2010), and thus, even transient changes in temperature due to heat waves or unusual extreme weather events could alter disease dynamics and put humans, other animals, and plants at risk. Invertebrate vector hosts and their pathogens could be greatly affected by temperature elevation because temperature has a large effect on their physiological processes including immune defense pathways and also the pathogen replication rate (e.g., Dittmar et al, 2014; Franke et al, 2017; Huey & Kingsolver, 1989; Kirk et al, 2018; Seppälä & Jokela, 2011).…”
Section: Introductionmentioning
confidence: 99%